Penerapan Kepemimpinan Instruksional Dalam Meningkatkan Kualitas Pendidikan di SMA IT Kota Balikpapan - Reza Mahendra Juniar; Dian Hidayati; Pujiati Suyata (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This study aims to analyze the application of instructional leadership in improving the quality of education in an Integrated Islamic High School in Balikpapan City. The main focus of the research is on instructional leadership process, school environment condition, and culture creation to improve education quality. The research method used is a qualitative approach with data collection techniques through in-depth interview, observation, and document analysis. The results showed that the instructional leadership process in Integrated Islamic High School includes the implementation of vision and mission based on Islamic values, continuous learning analysis and monitoring, and intensive support and supervision from the principal. The school environment, supported by an adaptive curriculum and excellent programs, as well as adequate facilities, creates a supportive work environment and improves the overall quality of education. In addition, the school culture formed through open communication, collaboration between educators and the example of the principal, creates a conducive and productive learning atmosphere for students. The findings of this study also provide practical recommendations for similar schools to improve the quality of education through inclusive and religious values-oriented leadership strategies.